Aquaponic : a modern farming system - Ibrahim Che Omar; Lee Seong Wei (2011)
This paper describes the potential of aquaponic as a poverty eradication tool in Malaysia. Although Malaysia is recognized as a developed country, poverty is still occurring among Malaysian, especially from rural area. Therefore, aquaponic - a modern farming system is being introduced to benefit the low income family. Aquaponic is the term that described the synergistic combination of aquaculture and hydroponic farming. Aquaponic system is comprised of two units, which is fish culture tank and plant growing area. This integrated system makes use of the rich nutrient wastes from cultured fish to cater the plant growth and in turn, the plan plays an important role to cleanse and re-oxygenate the water to be reused for the fish culture. A feasibility study to produce catfish and lettuce by aquaponic system has been carried out in involving 10 partcipants and the result has been found to be satisfying.